1992
DOI: 10.1590/s0074-02761992000500052
|View full text |Cite
|
Sign up to set email alerts
|

Nectomys squamipes (Rodentia: Cricetidae) as an experimental model for schistosomiasis mansoni

Abstract: Twenty specimens of Nectomys squamipes born in captivity, were infected with 500 cercariae by the transcutaneous route. Coprologic examinations were carried out from the 5th to 23rd week after infection. On the 7th, 8th, 12th, 16th, and 23rd weeks the animals were sacrificed and perfused. The oogram was performed in segments of the small intestine (proximal, medial and distal portions) and the large intestine. The average pre-patent period was of 42 days. The average number of eggs varied from 350 on the 6th w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
6

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 0 publications
1
18
0
6
Order By: Relevance
“…In this study, overall results confirm that N. squamipes is a permissive host to S. mansoni 17,18,20,32,33,34 . It must be also emphasized that S. mansoni adult worms might detect signals from their environment and responding appropriately in a state-dependent manner could greatly enhance its fitness 36 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, overall results confirm that N. squamipes is a permissive host to S. mansoni 17,18,20,32,33,34 . It must be also emphasized that S. mansoni adult worms might detect signals from their environment and responding appropriately in a state-dependent manner could greatly enhance its fitness 36 .…”
Section: Discussionsupporting
confidence: 78%
“…The authors showed that at week eight post-infection, the new strain was less pathogenic than the other two, since a lower number of hepatic granulomas and a smaller granuloma size were found 38 . Earlier studies demonstrated that N. squamipes could also be used as an alternative animal model in basic biological studies on schistosomiasis 20,34 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Souza et al (1992) verified that in a long-term infection period (between 12th and 16th post infection) there is a decrease toward females worms. However, these results differed from those found by Maldonado Jr. et al (1994) for N. squamipes under experimental conditions, where the sex ratio was well-balanced.…”
Section: Discussionmentioning
confidence: 68%
“…This species excretes viable eggs of the parasite during its hole life-span (RodriguesSilva 1988) and shows strong fitness to parasitism . Furthermore, N. squamipes has a high susceptibility to experimental infection (Souza et al 1992), reinfection (Maldonado Jr. et al 1994), and with a moderate pathogenic response (Silva & Andrade 1989).…”
mentioning
confidence: 99%
“…Among the extra-human definitive hosts of this parasite, rodents of the genera Nectomys and Holochilus are the most probable wild reservoirs taking into account: (1) their semiaquatic habits (Ernest & Mares 1986), which make them highly exposed to infection; (2) their wide geographic distribution (Bonvicino 1994) coincident with the distribution of schistosomiasis in Brazil; (3) presence of infected individuals in most of the endemic areas where they were investigated, despite of the low human prevalence -rodents frequently showing higher infection rates in relation to human populations (Rey 1993); (4) rodent tolerance to human presence, occurring near human dwellings. Several experimental studies also support the hypothesis that water-rats are probable wild reservoirs of S. mansoni, showing high susceptibility to infection (Borda 1972, Souza et al 1992, Maldonado Jr. et al 1994, Ribeiro et al 1998, somatic development hypertrophy of adult worms , elimination of viable eggs with high infectivity potential (Picot 1992), high infection persistence , low pathogenicity with efficient peri-ovular modulation and low tissue aggression (Silva & Andrade 1989), and ability to close the transmission cycle in semi-natural conditions (Antunes et al 1973, Carvalho et al 1976, Kawazoe & Pinto 1983. Infection of small mammals other than Nectomys and Holochilus by S. mansoni occurs only occasionally, especially in areas of high transmission levels.…”
mentioning
confidence: 75%